Do Deutscher Hifsverein ao Colégio Farroupilha/RS: Memórias e Histórias (1858-2008) (Revista Linhas, 2014)
BASTOS, Maria Helena Camara; JACQUES, Alice Rigoni; ALMEIDA, Dóris Bittencourt (Org.). Do Deutscher Hifsverein ao Colégio Farroupilha/RS: Memórias e Histórias (1858-2008). Porto Alegre: EDIPUCRS, 2013.